Exploring household water conservation behaviors in Saudi Arabia: A structural equation modeling approach - Abdulaziz I. Almulhim; Ismaila Rimi Abubakar (Journal of Open Innovation: Technology, Market and Complexity)
Water conservation is crucial for human sustainable development, particularly in the face of increasing global challenges such as freshwater scarcity, rapid urbanization, and climate change. This study employs structural equation modeling (SEM) to investigate water conservation behaviors among households in Saudi Arabia. Specifically, it examines the influence of household socioeconomic factors, sources of information, and government policies and programs on water conservation behaviors. A questionnaire survey was conducted among representative sample of households in Dammam city (n = 618). The collected data were analyzed using SEM to explore the relationships between variables and identify significant predictors of water conservation behaviors. Socioeconomic factors were found to have a significant influence on garden management practices (p = 0.001, β = 0.343), but not other water conservation practices. Public lectures and workshops were identified as the most preferred sources of information about water conservation practices (factor loading [λ] = 0.788). Participants indicate their support for public awareness campaigns for promoting water conservation, but they showed resistance to the idea of raising water tariffs (λ = 0.435) and implementing water conservation laws with fines for violators (λ = 0.318) as water conservation policies. This study provides a comprehensive analysis of the socioeconomic, informational, and policy factors influencing household water conservation in Saudi Arabia, offering actionable insights to design targeted, culturally sensitive, and sustainable water conservation strategies in arid regions, thereby contributing to the broader understanding of effective water resource management under challenging climatic and socioeconomic conditions. The study can help city administrators to promote sustainable water consumption behaviors and enlighten the public to adopt water conservation practices at home.